Motivation to quit smoking and acceptability of shocking warnings on cigarette packages in Lebanon - Layoun N; Salameh P; Waked M; Aoun Bacha Z; Zeenny RM; El Hitti E; Godin I; Dramaix M (Patient Preference and Adherence, 2017)
Nelly Layoun,1,2 Pascal Salameh,2,3 Mirna Waked,4 Z Aoun Bacha,5 Rony M Zeenny,6 Eric El Hitti,4 Isabelle Godin,1 Michèle Dramaix1 1Research Center in Epidemiology, Biostatistics and Clinical Research, School of Public Health, UniversitéLibre de Bruxelles, Brussels, Belgium; 2Doctoral School of Sciences and Technologies, Lebanese University, Beirut, Lebanon; 3Clinical and Epidemiological Research Laboratory, Faculty of Pharmacy, Lebanese University, Beirut, Lebanon; 4Department of Pulmonology, St George Hospital University Medical Center; Faculty of Medicine, Balamand University, Beirut, Lebanon; 5Department of Pulmonary and Critical Care Medicine, Hotel-Dieu de France, Beirut, Lebanon; 6Pharmacy Practice Department, School of Pharmacy, Lebanese American University, Byblos, Lebanon Introduction: Health warnings on tobacco packages have been considered an essential pillar in filling the gap of knowledge and communicating the health risks of tobacco use to consumers. Our primary objective was to report the perception of smokers on the textual health warnings already appearing on tobacco packages in Lebanon versus shocking pictures about the health-related smoking consequences and to evaluate their impact on smoking behaviors and motivation. Methods: A pilot cross-sectional study was undertaken between 2013 and 2015 in five hospitals in Lebanon. Participants answered a questionnaire inquiring about sociodemographic characteristics, chronic respiratory symptoms, smoking behavior and motivation to quit smoking. Only-text warning versus shocking pictures was shown to the smokers during the interview. Results: Exactly 66% of the participants reported that they thought shocking pictorial warnings would hypothetically be more effective tools to reduce/quit tobacco consumption compared to only textual warnings. Also, 31.9% of the smokers who were motivated to stop smoking reported that they actually had stopped smoking for at least 1 month secondary to the textual warnings effects. A higher motivation to quit cigarette smoking was seen among the following groups of smokers: males (odds ratio [OR] =1.8, P=0.02), who had stopped smoking for at least 1 month during the last year due to textual warning (OR =2.79, P<0.001), who considered it very important to report health warning on cigarette packs (OR =1.92, P=0.01), who had chronic expectoration (OR =1.81, P=0.06) and who would change their favorite cigarette pack if they found shocking images on the pack (OR =1.95, P=0.004). Conclusion: Low-dependent smokers and highly motivated to quit smokers appeared to be more hypothetically susceptible to shocking pictorial warnings. Motivation to quit was associated with sensitivity to warnings, but not with the presence of all chronic respiratory symptoms. Keywords: cigarette tobacco smoking, adult smokers, health warnings, cigarette packaging, graphic warning labels, textual warning labels